SAT0300 SERUM FROM "EARLY" SYSTEMIC SCLEROSIS PATIENTS ALREADY INDUCES THE ALTERNATIVELY ACTIVATED MACROPHAGE PHENOTYPE (M2) IN CULTURED HUMAN MONOCYTES. (2nd June 2020) - Soldano, S.; Tardito, S.; Paolino, S.; Patanè, M.; Gotelli, E.; Corallo, C.; Pizzorni, C.; Pacini, G.; Goegan, F.; Sulli, A.; Schenone, C.; Smith, V.; et al.
Abstract : Background: Alternatively activated (M2) macrophages seem to play a role in the fibrotic process of systemic sclerosis (SSc) as potential inducers of tissue fibrosis through their secretion of specific cytokines and chemokines, such as interleukin-10 (IL-10), macrophage derived chemokine (CCL-22) and pro-fibrotic metalloproteases (i.e. MMP9) (1-3). Objectives: To investigate the presence of circulating cells belonging to the monocyte lineage showing an M2 phenotype in SSc patients (pts) and possible correlation with the clinical parameters of the disease. Moreover, to investigate if the treatment of cultured monocytes isolated from healthy subjects with serum derived from early SSc pts may induce their in vitro polarization into M2 macrophages. Methods: Fifty female SSc pts (mean age 64±13 yrs), fulfilling the EULAR/ACR criteria, and 27 gender-matched healthy subjects (HSs, mean age 57±7 yrs) were considered at the Rheumatology Division of Genoa University after written informed consent. Nailfold videocapillaroscopy (NVC), serum SSc-related antibodies and skin involvement were investigated. Circulating cells belonging to the monocyte populations (CD45 + and CD14 + cells) were characterised by flow cytometry using specific surface markers of M2 phenotypes (CD204, CD206, CD163). Each SSc pt had been under stable treatment regimen for at least six months. Cultured monocytes, isolated by negative selection from peripheral blood mononuclear cells (PBMCs) of 8 HSs, stimulated for 48 hrs with 10% of serum of lcSSc pts with "Early" NVC pattern, as well as serum of dcSSc pts with "Active" and "Late" NVC patterns. Cultured monocyte human cell line (THP1) was differentiated into macrophages (5ng/ml of phorbol myristate acetate) and then stimulated with SSc sera. The expression of CD204, CD206 (M2 markers) and CD68 was investigated by immunocytochemistry, whereas MMP9 secretion was investigated by zymography. Statistical analysis was performed using Mann-Whitney and Kruskal-Wallis tests, and correlations were explored by bivariate Pearson's analysis. Results: In SSc pts the percentage of circulating M2 cells (CD14 + CD204 + CD163 + CD206 + cells) was significantly increased compared to both HSs and SSc pts not under immunosuppressive treatment (p<0.05) However, no correlation with skin involvement and SSc-related antibodies was observed. Cultured macrophages stimulated with SSc serum expressed CD204 and CD206 markers compared to the macrophages stimulated with HS serum (CD204 and CD206 double negative cells). Of note, the ability to express M2 markers was already evident in cultured macrophages stimulated with "Early" NVC SSc serum and their expression even increased in macrophages stimulated with "Active" and "Late" NVC sera together with the secretion of MMP9. Same results were observed also in cultured THP1-derived macrophages. Conclusion: The study confirmed that SSc pts are characterized by a significant increase of circulating M2 cells, suggesting their possible involvement in the pathogenesis of the disease. Interestingly, results insinuate that sera from SSc patients already in an "Early" NVC condition (sera known to contains specific profibrotic molecules such as cytokines, growth factors like TGFb1 or endothelin-1) seem able to induce in vitro a profibrotic M2 macrophage phenotype. References: [1]Cutolo M et al. ExpRevClin Immunol. 2019;15:753-64. [2]Stifano G et al. Curr Rheumatol Rep. 2016; 18:2. doi: 10.1007/s11926-015-0554-8. [3]Medeiros NI et al. Parasite Immunol. 2017;39: doi: 10.1111/pim.12446. Disclosure of Interests: Stefano Soldano: None declared, Samuele Tardito: None declared, Sabrina Paolino: None declared, Massimo Patanè: None declared, Emanuele Gotelli: None declared, Claudio Corallo: None declared, Carmen Pizzorni: None declared, Greta Pacini: None declared, Federica Goegan: None declared, Alberto Sulli Grant/research support from: Laboratori Baldacci, Carlotta Schenone: None declared, Vanessa Smith Grant/research support from: The affiliated company received grants from Research Foundation - Flanders (FWO), Belgian Fund for Scientific Research in Rheumatic diseases (FWRO), Boehringer Ingelheim Pharma GmbH & Co and Janssen-Cilag NV, Consultant of: Boehringer-Ingelheim Pharma GmbH & Co, Speakers bureau: Actelion Pharmaceuticals Ltd, Boehringer-Ingelheim Pharma GmbH & Co and UCB Biopharma Sprl, Maurizio Cutolo Grant/research support from: Bristol-Myers Squibb, Actelion, Celgene, Consultant of: Bristol-Myers Squibb, Speakers bureau: Sigma-Alpha